Penyuluhan Kesehatan dan Promosi Metode Cuci Tangan yang Benar di SD Negeri 6 Tamalanrea Kota Makassar - Nurambiya, Nurambiya; Nashrulloh, Dewi; Treasa, Adisty Dwi; Ilham, Radiah; Badaruddin, Badaruddin; Usviany, Veny; Abdullah, Abdullah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Washing your hands with soap is a sanitation action where humans clean their hands and fingers using water and soap to make them clean and break the chain of germs. This is done because hands are often agents that carry germs and cause pathogens to move from one person to another, either by direct or indirect contact. Health Education and Promotion of Hand Washing Methods Hand Washing with Soap aims to provide knowledge about how to wash hands properly and correctly using soap. The target of the counseling is students in Classes I, II and III of Tamalanrea State Elementary School 6. It is hoped that students will have the knowledge and practice as early as possible how to wash their hands correctly. This PkM method is health education and promotion of the correct way to wash hands by explaining what washing hands is, what is needed to wash hands, when to wash hands, the benefits of washing hands, and how to wash hands correctly. The results showed that after carrying out the PkM activities, the children at Tamalanrea State Primary School 6 were able to say, although not in detail, about washing their hands, what tools were used to wash their hands, and how to wash their hands correctly. The conclusion is that the outreach activities for the Clean and Healthy Living Behavior Program, especially Washing Your Hands with Soap, which were carried out for students at Tamalanrea State Elementary School 6, were quite successful because they were able to increase students' knowledge regarding Washing Your Hands with Soap before and after the Health Education and Promotion.